2018
DOI: 10.1007/s11357-018-0046-7
|View full text |Cite
|
Sign up to set email alerts
|

Report: NIA workshop on translating genetic variants associated with longevity into drug targets

Abstract: To date, candidate gene and genome-wide association studies (GWAS) have led to the discovery of longevity-associated variants (LAVs) in genes such as FOXO3A and APOE. Unfortunately, translating variants into drug targets is challenging for any trait, and longevity is no exception. Interdisciplinary and integrative multi-omics approaches are needed to understand how LAVs affect longevity-related phenotypes at the molecular physiologic level in order to leverage their discovery to identify new drug targets. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
(71 reference statements)
1
8
0
Order By: Relevance
“…Consistent with oxidative stress, in this study, significant correlations were also observed for other endogenous antioxidant enzyme family members, mitochondrial superoxide dismutase, SOD2, and CAT (Hayden & Tyagi, 2004), where they significantly decreased with age in plasma and liver. An overlap between proteins implicated in folate metabolism and proteins in immune related pathways was observed, consistent with recent studies (Ogg et al, 1997;Schork & Raghavachari, 2018).…”
Section: Folate Metabolismsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with oxidative stress, in this study, significant correlations were also observed for other endogenous antioxidant enzyme family members, mitochondrial superoxide dismutase, SOD2, and CAT (Hayden & Tyagi, 2004), where they significantly decreased with age in plasma and liver. An overlap between proteins implicated in folate metabolism and proteins in immune related pathways was observed, consistent with recent studies (Ogg et al, 1997;Schork & Raghavachari, 2018).…”
Section: Folate Metabolismsupporting
confidence: 91%
“…In C.elegans, a null mutation of the FOXO ortholog DAF-16 is associated with life extension, likely through the modulation of carbohydrate metabolism and by enhancing stress response (Murtaza et al, 2017;Ogg et al, 1997). In humans, genetic variations of FOXO3A are associated with healthspan and longevity and are highly prevalent in centenarians (Schork & Raghavachari, 2018). Interestingly, in this literature review, we found several agerelated proteins regulated by FOXO transcription factors (Morris et al, 2015), including proteins implicated in energy homeostasis (agouti-related neuropeptide (AGRP)), ROS detoxification (catalase (CAT), superoxide dismutase 2 (SOD2)), and epidermal growth factor receptor (EGFR) signaling pathway (Table S2).…”
Section: Foxo Signaling Pathwaymentioning
confidence: 99%
“…However, an important lesson learned from studying centenarians and their offspring is that there are factors that protect some individuals from conditions associated with older ages (Andersen et al, 2012; Ismail et al, 2016; Partridge et al, 2018; Sebastiani et al, 2013). Given the finding that centenarians seem relatively protected from age‐related conditions, it is naturally of interest to study genetic and molecular profiles of both centenarians and their offspring to determine the genetic basis as to how and why some people age more healthily than others, in an effort to ultimately discover treatments for age‐related disorders (Kaeberlein et al, 2015; Schork et al, 2018; Sebastiani & Perls, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that complex phenotypes are determined by multiple alleles functioning in combination (i.e., haplotypes), which should be extended to trans-genomic haplotypes and interactions between mtDNA-nDNA in future research [113][114][115]. With future developments in the integration of genomics, epigenomics, transcriptomics, proteomics, and metabolomics (-omics) data, there is greater hope that functional genetic variation in any pathway can be investigated for any phenotype, and in humans, on a more holistic system-biology level [1,2,116]. This kind of work will also help researchers plan for focused data-driven experiments aimed at explaining genotype-to-phenotype mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Geroscience research has been focused on understanding the molecular mechanisms driving the cellular and physiological functional decline that comes with increased age [ 1 , 2 ]. Understanding the aging process to develop geroprotective interventions that extend health, quality of life, and independence during the final decades of life is one goal of geroscience research [ 2 , 3 ]. Geroscience research has succeeded in identifying key biological pathways, labeled as “hallmarks or pillars of aging,” that drive the aging process [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%